Neoadjuvant anti-programmed death-1 immunotherapy by pembrolizumab in resectable non-small cell lung cancer: first clinical experience - Eichhorn, Florian; Klotz, Laura Valentina; Kriegsmann, Mark; Bischoff, Helge; Schneider, Marc; Muley, Thomas; Kriegsmann, Katharina; Haberkorn, Uwe; Heußel, Claus Peter; Savai, Rajkumar; Zörnig, Inka; Jäger, Dirk; et al. (Lung cancer, 2021)
Objectives - A phase II trial investigating the therapeutic effect of neoadjuvant programmed cell death 1 (PD-1) inhibitor pembrolizumab (MK-3475, KEYTRUDA®) administered prior to surgery for the treatment of non-small cell lung cancer (NSCLC) has been conducted (NCT03197467). We report the first clinical results of a planned interim safety analysis after 15 patients were enrolled. - Material and methods - Patients with resectable NSCLC stage II/IIIA were included. Two cycles of pembrolizumab (200mg intravenously once every 3 weeks) were administered prior to surgery. The primary objectives were to assess the feasibility and safety of neoadjuvant pembrolizumab therapy and to evaluate antitumor activity. We analyzed the clinical parameters as well as pathological and radiological tumor response data. - Results - The NSCLC histology was adenocarcinoma for 13 patients and squamous cell carcinoma for 2 patients. All patients but two underwent 2 cycles of pembrolizumab prior to surgery. Four patients (27 %) presented a major pathologic response. Significant tumor target response in positron emission tomography computed tomography (PET-CT) was detected in all 4 pathologic responders. Nevertheless, the PET findings mismatched the tumor load in some patients. A PD-L1 expression ≥10 % in the pretreatment biopsy was associated with at least major pathologic response. Five patients (33 %) presented grade 2-3 treatment related adverse events (TRAE), the overall postoperative morbidity was 7 % and 30-day mortality was 0 %. - Conclusion - Neoadjuvant pembrolizumab is a feasible therapy in surgical lung cancer patients. It was associated with tolerable toxicity and did not compromise tumor resection.
Gesehen am 26.08.2021